Improved definition of gas sand using elastic impedance attribute on an avo data over an x field, Nigerian Niger delta - M.C, Ohakwere-Eze; M. U., Igboekwe; G.U, Chukwu (International Journal of Advanced Geosciences, 2019)
Elastic impedance (EI) inversion is considered one of the newest methods being used today in geophysical interpretation. Preliminary interpretation carried on the well logs revealed a hydrocarbon bearing sand from 8780 to 8900 ft. The average porosity value is 39% which suggest good porosity values for oil and excellent for gas reservoirs. The matched total resistivity values are likewise very high at about 90 â„¦m with a very low density at that depth. The logs were modelled by creating the EI near and EI far logs from the input Vp, Vs and density logs at a defined angle of incidence of 2.5 for near angle and 45.0 for far angle. The EI Far log is lower than the EI Near log in the interpreted depth but higher in the rest of the log. This is further revealed in the crossplot showing the mapped gas sand at depth between 8780 and 8900ft. Two Range limited stack were created from the seismic gathers with the first/near offset stack at 64m and second/far offset stack at 196m. From each stack, a model each was created to get the near EI model and far EI model respectively from which inversion was done to generate the near and far inversion results. There is an improved definition of the gas sand on the far angle inversion with a stronger contrast represented by low values at the mapped seismic time window which corresponds to the mapped gas sand at same depth. This was further revealed on the crossplot. Inserting the crossplot on the near-Inversion volume with the mapped zone, the visible top of gas on the zone of interest was noticed. This zone confirmed where the elastic impedance at far-offsets is lower than the elastic impedance at near-offsets moreover agreed with the Elastic Impedance results on the logs. The Elastic Impedance attribute and its inversion technique has shown it is a strong and suitable tool in exploitation of gas zones as it has optimized the area of the gas zone approved by well logging process.Â Â